Improved Diagnosis of Prosthetic Joint Infection by Culturing Periprosthetic Tissue Specimens in Blood Culture Bottles - Trisha N. Peel (American Society for Microbiology, 2016)
ABSTRACT Despite known low sensitivity, culture of periprosthetic tissue specimens on agars and in broths is routine. Culture of periprosthetic tissue samples in blood culture bottles (BCBs) is potentially more convenient, but it has been evaluated in a limited way and has not been widely adopted. The aim of this study was to compare the sensitivity and specificity of inoculation of periprosthetic tissue specimens into blood culture bottles with standard agar and thioglycolate broth culture, applying Bayesian latent class modeling (LCM) in addition to applying the Infectious Diseases Society of America (IDSA) criteria for prosthetic joint infection. This prospective cohort study was conducted over a 9-month period (August 2013 to April 2014) at the Mayo Clinic, Rochester, MN, and included all consecutive patients undergoing revision arthroplasty. Overall, 369 subjects were studied; 117 (32%) met IDSA criteria for prosthetic joint infection, and 82% had late chronic infection. Applying LCM, inoculation of tissues into BCBs was associated with a 47% improvement in sensitivity compared to the sensitivity of conventional agar and broth cultures (92.1 versus 62.6%, respectively); this magnitude of change was similar when IDSA criteria were applied (60.7 versus 44.4%, respectively; P = 0.003). The time to microorganism detection was shorter with BCBs than with standard media (P < 0.0001), with aerobic and anaerobic BCBs yielding positive results within a median of 21 and 23 h, respectively. Results of our study demonstrate that the semiautomated method of periprosthetic tissue culture in blood culture bottles is more sensitive than and as specific as agar and thioglycolate broth cultures and yields results faster. IMPORTANCE Prosthetic joint infections are a devastating complication of arthroplasty surgery. Despite this, current microbiological techniques to detect and diagnose infections are imperfect. This study examined a new approach to diagnosing infections, through the inoculation of tissue samples from around the prosthetic joint into blood culture bottles. This study demonstrated that, compared to current laboratory practices, this new technique increased the detection of infection. These findings are important for patient care to allow timely and accurate diagnosis of infection.